IMPLEMENTATION OF LBPH ALGORITHM IN AUTOMATIC DOOR OPENING SYSTEM WITH FACIAL RECOGNITION - Stepanus.S, Ronaldo; Satria, Beni; Dani, Ahmad (Cattleya Darmaya Fortuna, 2025)
Automatic door opening system with facial recognition is an application that is widely used to improve security and comfort in various fields, such as offices, homes, and other limited areas. This study implements the Local Binary Pattern Histogram (LBPH) algorithm in an ESP32-based automatic door opening system integrated with an OV2640 camera. LBPH was chosen because of its superiority in recognizing faces even with varying lighting conditions and imperfect image quality. This system works by capturing facial images through an OV2640 camera, then processing the image using the LBPH algorithm to extract facial features. The results of facial recognition are then sent to the ESP32 which controls the automatic door locking system. In this implementation, the ESP32 is used as a microcontroller to connect the camera, data processing, and control the door actuator. Tests were conducted to measure the accuracy of facial recognition and system performance in opening the door. The test results show that the system can recognize faces with a high level of accuracy and open the door automatically in a short time, thereby increasing the efficiency and security of the system.